(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Electronic Human Resource Management (E-HRM) plays a crucial role in enhancing operational efficiency, decision-making and coordination within higher education institutions. Open universities, especially those offering skill-based programs, face challenges due to decentralized operations, geographically dispersed staff and varied administrative processes. This study presents a conceptual digital E-HRM framework for such institutions using secondary data, integrating student assessment (theory, practical, viva), course content delivery and evaluation processes. The framework draws on E-HRM typologies, technology acceptance concepts and insights from higher education practices and Indian skill development policies. Findings indicate that combining operational, relational and transformational E-HRM approaches with a structured skill-based course roadmap improves administrative efficiency, faculty management and program delivery quality. The framework also addresses digital readiness, process fragmentation and user adoption challenges, offering a strategic guide for implementing digital HR systems in open universities. The study provides a systematic approach to enhancing HR effectiveness in skill-based education and informs future empirical research.